PROSES AGLOMERASI DAN DAMPAK OPERASIONAL PADA PEMBAKARAN CANGKANG SAWIT DALAM UNGGUN TERFLUIDISASI - Wahyu, Haifa; Affendi, M. (Teknologi Indonesia, 2011)
The use of palm shell as fuel in fl uidized bed may be a better choice than that of coal in terms of carbon emission elimination due to its more environmentally friendly properties. But in reality it will cause operational problems. Continuous combustion results in agglomeration of the sand bed, which triggers defl uidization and hence operational shut down. This paper presents a combustion test of palm shell in a laboratory scale fluidized bed furnace with the capacity of 15 kg/hr located at the Research Centre of Physics, Indonesian Institute of Sciences. The results show that continuous burning of palm shell will lead to agglomeration in the furnace, especially when the temperature was above 800oC. The alkali and chlorine material contained in the biomass ash will interact with calcium silicate contained in the sand bed of FBC during combustion. Therefore the mixture of ash and silicate produces clinker that lowers its melting temperature down to about 800C.